E-COMMERCE SPAREPART MOTOR MENGGUNAKAN METODE WATERFALL (STUDI KASUS: BENGKEL PROKLAMASI JAYA MOTOR) - Eka Rini Yulia; Siti Ernawati; Risa Wati (Universitas Bina Sarana Informatika, 2018)
Abstract – E-commerce is defined as an act of buying and selling as well as marketing and service of products, services, and information through a variety of computer networks. In this research, the running system motorcycle spare parts sales at Proklamasi Jaya Motor repair shop is still done manually. It causes the system to be less effective. In this point, E-commerce is one of the most important elements in the development of a business or effort, hence researchers create an information system, in the form of e-commerce, to manage online sales system spare part motorcycle at Proklamasi Jaya Motor repair shop. The purpose of making this system is to help increase sales and improves customers’ satisfaction because the customers do not need to come directly to the repair shop. Key Word: E-Commerce, Motorcycle Spare Parts, and Waterfall